SNP and Haplotype characterisation of Apobec 3G, a protein invovled in Retroviral defence, in Black South Africans - Ramdin, Roshilla (My University, 2013)
Heritable variation is important in disease progression, therefore its association with HIV/AIDS was analyzed. APOBEC3G is a unique cellular gene that influences HIV infectivity. It belongs to family of cytidine deaminases and is both an RNA and DNA editing enzyme. APOBEC3G is a good candidate for HIV restriction because it allows the expression of an antiviral phenotype in non-permissive cells consequently this innate immune defense may provide the basis for the design of new therapies for HIV. Variation in the upstream non-coding region of APOBEC3G was studied. Six base variants were found at positions -90, -163, -166, -571, -590 and -821. In addition, promoter analysis identified promoters in the upstream non-coding region. Indirect genotyping assays were developed to genotype the participants at -571 and H186R. The frequency of -571 GG was 70 %. The frequency of the TT genotype of H186R was 20 %. The GG genotype was selected against in the HIV + group of the study participants. This is indicative that this SNP has disease modifying effects. The TT genotype was related to increased progression to AIDS confirming the results of previous studies.